Complete Maxillary Crossbite Correction with a Rapid Palatal Expansion in Mixed Dentition Followed by a Corrective Orthodontic Treatment - Orlando Motohiro Tanaka; Isabelle Adad Fornazari; Ariane Ximenes Graciano Parra; Bruno Borges de Castilhos; Ademir Franco (Case Reports in Dentistry)
This case report presents the interceptive orthodontic treatment of a boy, aged 8 years 4 months with a Class I malocclusion with severe transverse maxillary deficiency and complete maxillary crossbite and correction using Haas expansion and fixed appliance. The treatment goals were to correct the posterior crossbite and anterior crossbite and restore the normality of the dentition and occlusion. In phase I, the patient was treated with a modified Haas-type palatal expander, which provided a clinically significant palatal expansion and increased the maxillary arch perimeter with favorable conditions for orthodontic treatment with fixed appliances in phase II. The optimization of E-space and the use of intermaxillary Class III elastics helped to maintain the mandibular incisors upright. A removable wraparound type appliance and a bonded lingual canine-to-canine retainer were used as retention. Although the literature has reported a high rate of relapse after palatal expansion, after 2 years 9 months of posttreatment follow-up, the occlusal result was stable and no skeletal reversals could be detected.